Prediction of pavement fatigue cracking at an accelerated testing section using asphalt mixture performance tests. Issue Volume 19:Issued 3(2018) (4th March 2018) - Ozer, Hasan; Al-Qadi, Imad L.; Singhvi, Punit; Bausano, Jason; Carvalho, Regis; Li, Xinjun; Gibson, Nelson
Abstract: Cracking in asphalt concrete (AC) layers is among the driving modes of flexible pavement deterioration. Material properties, along with structural layer characteristics and external factors such as vehicular and environmental loading, govern cracking mechanisms in flexible pavements. Current practice of AC and pavement structural design methods does not allow for direct characterisation of AC impact on crack damage initiation and propagation. Asphalt concrete performance tests are the essential components of performance-related and performance-based specifications, for which they can be used either for screening AC to minimise deterioration risks or to directly predict specific modes of pavement deterioration. This paper evaluates commonly used performance tests intended to characterise AC fracture resistance. A multi-step evaluation protocol was applied using various statistical techniques to determine the discrimination ability of each test method outcome criterion as well as strength of correlation to field performance. The results from full-scale accelerated pavement test (APT) sections were used to correlate with the results obtained from various laboratory performance tests. Mixes used in the study contained various levels of reclaimed asphalt pavement and recycled asphalt shingles with a recycled binder ratio up to 40%. It was shown that the flexibility index parameter obtained from the Illinois semi-circular bending (IL-SCB) test, also referred to as the Illinois Flexibility Index Test (I-FIT), resulted in the highest number of subsets and consistent ranking with APT field performance, indicating a high discrimination potential. Even though two of the overlay test's criteria resulted in fewer subsets, they also provided a consistent ranking with APT field performance. Composite scores indicate that the overlay test criteria and flexibility index from the I-FIT had the highest strength of correlation to field performance.